1949
DOI: 10.1104/pp.24.3.455
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Rootstock on the Mineral Composition of Valencia Orange Leaves

Abstract: Rootstocks have been shown (7,8, 9,11,13) to exert an influence on tree growth, disease resistance, and fruit quality factors of various types of citrus. Recent work in California (5,6) in which the leaves of orange, grapefruit, and lemon trees on a large number of different rootstocks were analyzed for several nutritive elements, strongly suggests that the amounts of these minerals in the scion leaves may be affeeted by the rootstock used.Since one of the objectives of the nutritionial research program at thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1950
1950
1982
1982

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…These results on boron accumulation for these two rootstocks are in agreement with observations by other workers (13,23,26). Likewise, the boron values for Valencia and grapefruit in the control plot are similar to those reported for this area by REUTHER et al (24).…”
Section: Relative Accumulation Of Ions In Leaves Twigs Trunk and Rsupporting
confidence: 93%
See 3 more Smart Citations
“…These results on boron accumulation for these two rootstocks are in agreement with observations by other workers (13,23,26). Likewise, the boron values for Valencia and grapefruit in the control plot are similar to those reported for this area by REUTHER et al (24).…”
Section: Relative Accumulation Of Ions In Leaves Twigs Trunk and Rsupporting
confidence: 93%
“…The average magnesium content of leaves of both scions on sour orange was 0.35% of the dried leaves and that of the same scions on Cleopatra was 0.18%. These values for magnesium are similar to those reported for Texas by REUTHER et al (24) and the differences between rootstocks are similar to those reported by other workers (14,26). There appears to be no evidence of magnesium deficiency in these leaves; Shary Red on sour orange rootstock, which showed excessive bronzing, had more magnesium than other combinations showing less bronzing.…”
Section: Relative Accumulation Of Ions In Leaves Twigs Trunk and Rsupporting
confidence: 92%
See 2 more Smart Citations
“…The drying, grinding (in a semi-micro Wiley mill equipped with a nickel-coated screen), storage, and analysis were all carried out as previously described (13,14 Results and discussion Iron was assumed to be a general surface contaminant and was used as an indicator of efficacy of washing in initial tests. Since nearly all citrus leaves have on them visible dust particles, no samples were analyzed without some washing treatment.…”
Section: Methodsmentioning
confidence: 99%